Effect of Ethical Leadership, Organizational Justice and Psychological Empowerment toward Job Satisfaction of Employees at PT PJB Unit PJB Academy - Denik Putri Perdani; Nuri Herachwati (Budapest International Research and Critics University, 2022)
The purpose of this paper is to examine the effect of ethical leadership, organizational justice and psychological empowerment on job satisfaction. This study uses a quantitative approach by conducting a survey through a questionnaire. The data were statistically analyzed using SmartPLS to test the research hypothesis. The findings of this study are ethical leadership has been shown to have a positive and significant effect on job satisfaction, organizational justice has been shown to have a positive and significant effect on job satisfaction, but psychological empowerment has not been shown to have a positive and significant effect on job satisfaction. The results of this study can be a reference for organizations in order to increase employee job satisfaction in the midst of the challenges of the transformation of the company that is being carried out. Factors of leadership and organizational justice must receive special attention so that employees continue to work and feel satisfaction at work. This study presents empirical evidence in the context of an organization engaged in education and training services about what variables have a positive and significant effect on employee job satisfaction.